Efficacy and Safety of Peginterferon Alfa‐2a (40KD) in Children With Chronic Hepatitis B: The PEG‐B‐ACTIVE Study. Issue 5 (8th October 2018) - Wirth, Stefan; Zhang, Hongfei; Hardikar, Winita; Schwarz, Kathleen B.; Sokal, Etienne; Yang, Weibo; Fan, Huimin; Morozov, Vyacheslav; Mao, Qing; Deng, Hong; Huang, Yang; Yang, Lei; et al.
Abstract : Children with chronic hepatitis B (CHB) represent an area of unmet medical need, attributed to increased lifetime risk of CHB sequelae and limited therapeutic options compared with adult CHB patients. The PEG‐B‐ACTIVE (NCT01519960) phase III study evaluated peginterferon (PegIFN) alfa‐2a treatment in children aged 3 to <18 years with CHB. A total of 161 hepatitis B e antigen (HBeAg)‐positive immune‐active patients without advanced fibrosis (AF)/cirrhosis were randomized (2:1) to PegIFN alfa‐2a (Group A, n = 101) or no treatment (Group B, n = 50); patients with AF were assigned to PegIFN alfa‐2a (Group C, n = 10). PegIFN alfa‐2a was administered for 48 weeks by body surface area (BSA) category, based on 180 μg/1.73 m 2 . HBeAg seroconversion rates at 24 weeks posttreatment were significantly higher in Group A (25.7% vs. 6%; P = 0.0043), as were the rates of hepatitis B surface antigen (HBsAg) clearance (8.9% vs. 0%; P = 0.03), hepatitis B virus (HBV) DNA <2, 000 IU/mL (28.7% vs. 2.0%; P < 0.001) or undetectable (16.8% vs. 2.0%; P = 0.0069), and alanine aminotransferase (ALT) normalization (51.5% vs. 12%; P < 0.001). Safety, including incidence of ALT flares and neutropenia, was comparable to the established PegIFN alfa‐2a profile in HBV‐infected adults or hepatitis C virus‐infected children. Changes in growth parameters were minimal during treatment and comparable to those in untreated patients. Safety and efficacy outcomes in Group C were in line with Group A. Conclusion: PegIFN alfa‐2a treatment of children in the immune‐active phase of CHB was efficacious and well tolerated, and associated with higher incidence of HBsAg clearance than in adults. This represents an important advance to the treatment options for children with CHB.